Digitized Diaries - Hunter, David (The Diary Index, 2015)
This list of open access, digitized diaries is designed to assist students and scholars interested in studying diaries.
Keywords: _open access

The Noise-Arch Archive (2011)
This collection is a compilation of underground/independently-released cassette tapes from the days when the audio cassette was the standard method of music sharing... generally the mid-eighties through early-nineties. The material represented includes tape experimentation, industrial, avant-garde, indy, rock, diy, subvertainment and auto-hypnotic materials. Much of this material defies category, and has therefore not been given one. The bulk of the tapes in this library were donated to the project by former CKLN FM radio host Myke Dyer in August of 2009. The original NOISE-ARCH site was hosted and maintained by Graham Stewart and Mark Lougheed.
Keywords: _open access

The Maryland Motherlode: Births, Marriages, Deaths, and Naturalizations (Reclaim The Records)
Keywords: _open access

Henry Kissinger: The Declassified Obituary - National Security Archive
Keywords: _open access

CIA Reading Room Historical Collections
declassified documents from the Cold War
Keywords: _open access

New Deal (National Archives, 2016)
Links to web sites relating to the New Deal era useful for research on New Deal agriculture, labor, and arts programs. The New Deal , Painting/Mural by Conrad A. Albrizio. Dedicated to President Roosevelt. Placed in the auditorium of the Leonardo Da Vinci Art School, 149 East 34th Street, New York, New York,& ca. 1934 (FDR Presidential Library NLR-PHOCO-A-59333) Contents NARA Resources Other Resources NARA Resources "Archival Vintages for The Grapes of Wrath" Daniel Nealand's Prologue article shows how John Steinbeck used WPA documentary source material provided by Thomas E.
Keywords: _open access

Herbert Hoover Papers - Anonymous (The Herbert Hoover Presidential Library and Museum, 2017)
The papers of Herbert Hoover had been accumulating since 1919 at the Hoover Institution on War, Revolution, and Peace at Stanford University. In 1960 Hoover decided to donate materials beginning with his time as Secretary of Commerce onwards to the Herbert Hoover Presidential Library. The papers are arranged into five groups. Hoover Papers [accordion classes="" id="903" expand_first="false"][/accordion]
Keywords: _open access

The Valley of the Shadow: Two Communities in the American Civil War
Keywords: _open access

AARDOC: African-American Religion: A Documentary History Project Home Page
Keywords: _open access

UW-Madison Libraries Collections
Keywords: _open access

American Baptist Historical Society (American Baptist Historical Society, 2023)
The American Baptist Historical Society (ABHS) holds the archives and serves as the historical interpreter of a major religious denomination — American Baptist Churches USA — made up of 4,900 churches and 1.2 million people. ABHS archival collections include records from many different Baptist organizations in North America and around the world. As the oldest Baptist historical society (founded in 1853) with the largest and most diverse collection of Baptist historical material, our holdings are of irreplaceable value to church, national, and global history. ABHS serves as keeper of the record of the modern missionary movement. Our shelves hold unparalleled resources documenting African-American church associations, women’s work, local church and association minutes, and the social gospel movement. We publish the oldest Baptist journal, Foundations, interpreting for modern readers the lives and issues of the past that shape who we are today.
Keywords: _open access

Daniel A. P. Murray Pamphlet Collection (Library of Congress)
"African American Perspectives" gives a panoramic and eclectic review of African American history and culture and is primarily comprised of two collections in the Rare Book and Special Collections Division: the African American Pamphlet Collection and the Daniel A.P. Murray Collection with a date range of 1822 through 1909. Most were written by African-American authors, though some were written by others on topics of particular importance in African-American history. Among the authors represented are Frederick Douglass, Ida B. Wells-Barnett, Benjamin W. Arnett, Alexander Crummel, Emanuel Love, Lydia Maria Child, Kelly Miller, Charles Sumner, Mary Church Terrell, and Booker T. Washington, among others.
Keywords: _open access

African American Women Writers of the 19th Century - Divisions, Schomburg Center Research (NYPL)
African American Women Writers of the 19th Century guide includes a digital collection of published works by 19th-century black women writers, biographies for each author, citations and much more
Keywords: _100+; _open access

Houston Mutiny and Riot Records (South Texas College of Law Houston Digital Collections)
Keywords: _open access

National WWI Museum and Memorial (National WWI Museum and Memorial)
The National WWI Museum and Memorial's online collections database allows you to search digital records of our global collection that began in 1920.
Keywords: _open access

Independent Voices
About this Collection: Independent Voices is an open access digital collection of alternative press newspapers, magazines and journals, drawn from the special collections of participating libraries. These periodicals were produced by feminists, dissident GIs, campus radicals, Native Americans, anti-war activists, Black Power advocates, Hispanics, LGBT activists, the extreme right-wing press and alternative literary magazines during the latter half of the 20th century. Independent Voices is ma...
Keywords: _open access

Black Freedom Struggle - ProQuest
Open to everyone at blackfreedom.proquest.com
Keywords: _open access

American Prison Newspapers, 1800s-present: Voices from the Inside - JStor
Overview On March 24, 1800, Forlorn Hope was published within a prison in New York state, edited by an incarcerated person. In the intervening 200+ years, over 700 prison newspapers have been published from U.S. prisons in all fifty states. American Prison Newspapers will bring together hundreds of these periodicals from across the country into one collection that will represent penal institutions of all kinds, with special attention paid to women-only institutions. With the United States in...
Keywords: _open access

Historical Statistical Abstracts of the US - US Census Bureau (Census.gov)
Comprehensive summary of statistics on the social, political and economic conditions of the United States from 1878 to 2012.
Section: Government
Keywords: _open access

Early Americas Digital Archive
A collection of electronic texts originally written in or about the Americas from 1492 to approximately 1820.
Keywords: _open access

Documenting the American South
Texts, images, and audio files related to southern history, literature, and culture. Subjects covered include church history, African American history, North Carolina state history, oral and social histories, and more.
Keywords: _open access

Black Thought and Culture - Alexander Street Press
Collection d’écrits (autres que fictionnels) provenant de personnalités américaines noires majeures issues du monde politique, religieux, journalistique et autre.
Keywords: _NO SOFIA; _open access

Women Working, 1800-1930 (CURIOSity Digital Collections)
An exploration of women's impact on the economic life of the United States between 1800 and the Great Depression.
Keywords: _open access

National Archives - The U.S. National Archives and Records Administration
Keywords: _open access

Eugenics Archive
Keywords: _open access

Chronicling America - National Endowment for the Humanities (Library of Congress)
Search America's historic newspaper pages from 1770-1963 or use the U.S. Newspaper Directory to find information about American newspapers published between 1690-present.
Keywords: _open access

Ad*Access / Digital Collections / Duke Digital Repository (Duke Digital Collections)
Over 7,000 U.S. and Canadian advertisements covering five product categories - Beauty and Hygiene, Radio, Television, Transportation, and World War II propaganda - dated between 1911 and 1955.
Keywords: _open access